Information model and delivery system for improving the structure of industry in the digital economy - Rustamov Alisher Bakhodirovich (THE INNOVATION ECONOMY, 2026)
In the context of the digital economy, the issues of increasing the efficiency of industrial sectors and improving their structure are relevant. The article analyzes the possibilities of strengthening integration between industrial enterprises, optimizing production processes, and ensuring the efficient use of resources by forming a database based on information technologies. The results of the study are important in developing a strategy for digitizing industry, planning resources, and strengthening cross-sectoral cooperation. The conclusion emphasizes the priority of the integrated use of information resources and a data-based management approach to improving the industrial structure.